PENGARUH BERBAGAI KONSENTRASI SARI DAGING BUAH APEL (Molus domestica) TERHADAP KARAKTERISTIK DAN HASIL UJI ORGANOLEPTIK NATA DE APPLE - C. Sudarwati; Susie Amilah (FMIPA : Universitas PGRI Adi Buana, 2014)
This study aims to prove the effect of the concentration of fruit juice puch as nata de apple production materials to the production of nata,suppleness and organoleptic characters.The design used in this study was a completely randomized design (CDR) consisting of 3 perlakuan namely 500 gr,750 gr, 1000 gr.1 liter each were taken and repeated 6kali and added sugar 10%, urea 0,5% and 10% starter.The results showed the concentr ation of water and fruit juice apple significantly (p>0,05) on the influence the textur of nata with the highest combination of treatment 750 gram,and the lowest yield on treatment 500 gram.Concentrasi of water and fruit apple was also significanty (p>0,05) on the production of nata with combination treatment 750 gram,for odor and flavor character,but for the color of the panelists preferred the combination treatment nata 500 gram. Keywords: Molus domestica, Nata, Production, Texture organoleptik